2018
DOI: 10.1093/ckj/sfy088
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs and challenges for follow-up and treatment of autosomal dominant polycystic kidney disease: the paediatric perspective

Abstract: Awareness is growing that the clinical course of autosomal dominant polycystic kidney disease (ADPKD) already begins in childhood, with a broad range of both symptomatic and asymptomatic features. Knowing that parenchymal destruction with cyst formation and growth starts early in life, it seems reasonable to assume that early intervention may yield the best chances for preserving renal outcome. Interventions may involve lifestyle modifications, hypertension control and the use of disease-modifying treatments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 102 publications
(126 reference statements)
0
15
0
1
Order By: Relevance
“…Due to the side effects and disappointing results in adults, mTOR inhibitors have no place for treatment in children with ADPKD as well (16). Thus, none of our patients were on routine treatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to the side effects and disappointing results in adults, mTOR inhibitors have no place for treatment in children with ADPKD as well (16). Thus, none of our patients were on routine treatment.…”
Section: Discussionmentioning
confidence: 96%
“…It is well-known that disease progression can be prevented by modifiable factors including proteinuria and hypertension (2,16). In a meta-analysis, Marlais et al have found that 20% of children with ADPKD have HT (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, several limitations for such strategies are to be taken into consideration. Although different prognostic indicators have been identified in adults 16,23 , no stratification risk factors for progression are validated for children 10 . Nevertheless, because parenchymal destruction already occurs under the cover of compensated GFR values 27 , such indicators are required in order to accurately identify patients at risk for rapid progression.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, data on the natural history of and prognostic indicators for childhood ADPKD are both largely lacking and urgently needed [10][11][12] . The Tolvaptan Efficacy and Safety in Management of ADPKD and Its Outcomes (TEMPO) 3:4 trial is one of the largest studies conducted in the field (N = 1445) 6 .…”
mentioning
confidence: 99%
“…Ein Teil der Patienten zeigt bei der ADPKD ein rasches Fortschreiten der Erkrankung. Diese Patienten könnten von einer frühen Therapie profitieren [9,17].…”
Section: Klinische Symptome Im Kindesalterunclassified